STUDI KELAYAKAN USAHA KESEHATAN GIGI SEKOLAH (UKGS) DI MADRASAH IBTIDAIYAH MUHAMMADIYAH LEUWILIANG KABUPATEN BOGOR - Syahrani, Alifia; ulfah utami; Tri Widyastuti; Siti Fatimah (Poltekkes Kemenkes Bandung, 2024)
The group of school-age children who are vulnerable to dental and oral diseases are among the target subjects in efforts to improve health and prevent disease. The government is making efforts to improve health and prevent dental and oral disease in elementary school children, one of which is through the UKGS (School Dental Health Business) program. The aim of this research is to provide an overview of the UKGS (School Dental Health Business) feasibility study at elementary school (SD) level at MIM Leuwiliang, Bogor Regency. The method used in this research is qualitative descriptive research. Data was collected through in-depth interviews, field observations and comprehensive documentation. Data validity is checked through triangulation of data checking to ensure accuracy. The research results show that several aspects do not meet business feasibility standards, namely the organizational management aspect which experiences a shortage of human resources, and operational technical aspects which note a lack of facilities to support the UKGS program. So, from these aspects, this UKGS Feasibility Study was declared unfit to continue without significant improvements.